Organización de eventos culinarios y el turismo gastronómico en el cantón Urdaneta - Bustamante Cevallos, Kerly Antonela (2022)
The present investigation was carried out in the Urdaneta canton, province of Los Ríos, with the purpose of identifying the main food products of the gastronomic fairs of Urdaneta that are exposed as an attraction of the culinary culture of the canton, which will allow the Urdanetense community to spread their gastronomic traditions by organizing events. Ecuador is a diverse country with a wide range of food and beverage preparation methods. For this reason, gastronomic tourism offers visitors the opportunity to get closer and learn more about the culinary culture that characterizes each region of the country, as well as to obtain a closer knowledge and learn about the recipes of traditional dishes of the past. Nowadays, gastronomic fairs are held periodically in Ecuador with the aim of promoting gastronomic tourism as a source of economic and tourist growth for the country, as well as helping the used, maintaining the culinary identity, and boosting the Food sovereignty through the consumption of healthy foods offered by ancestral cuisine. It should be noted that the gastronomy the Urdaneta canton has many secrets that must be shared with other people. This research has a mixed approach, in order to obtain relevant and precise information on the main food products that are exhibited in the gastronomic fairs of the Urdaneta canton, the deductive and inductive method was applied, as well as the survey and interview techniques to the Urdanetense population. and visitors, in which favorable results were obtained.